Between political discourse and spiritual force. Foundation of the awajún and wampis indigenous organizations (1977-1979) - Romio, Silvia (2014)
The present article proposes an ethno-political analisis of the conceptof indigenous organization. The Huambisa Aguaruna Council(HAC) was the first Awajun and Wambis indigenous organization,which at the end of the seventies achieved to be the representant of almost all of the rivers in the Condorcanqui district (Amazonas region). This study seeks to understand how this first phase of construction of indigenous organization was characterized by the definition of a new form of leadership, in which a new generation of indigenous leaders showed great ability in negotiating concepts of ancestral life with new abilities and ideas learned through the interaction with the outside world. As such this new generation could be a bridge in between the expectations of the native communities and the imposed demands by Peruvian institutions.